MENINGKATKAN KOMPETENSI GURU MELALUI PELATIHAN P5 BERBASIS STEM: WORKSHOP KELOMPOK KERJA GURU SEKOLAH DASAR KOTA BEKASI - Setiawan, Bramianto; Awalina Barokah; Djoko Nugroho; Acep Ega Wihara; Frisya Naomi Nurezalita; M.S., Zulela (Universitas PGRI Adi Buana Surabaya, 2025)
Pancasila Student Profile Strengthening Project (P5) is a framework designed to integrate Pancasila values ​​into the learning process. With the curriculum transformation that leads to the development of student character, it is important for teachers to have a deep understanding of the implementation of P5. This training aims to improve the competence of teachers who are members of the Teacher Working Group (KKG) in Bekasi City in designing and implementing P5 based on the STEM (Science, Technology, Engineering, and Mathematics) approach. This activity is carried out in the form of intensive training and mentoring involving simulations, discussions, and direct practice. The evaluation results show that participants are able to integrate the STEM approach in the planning and implementation of P5 effectively. This article describes the methods, implementation, and impact of this training on strengthening teacher competence.